MUSYKILAATU AT-THALIBAH FII TA’LIIMI MAHAARATUL QIRAAH LISSHAFI AT-TSAMIN BI MADRASAH TSANAWIYYAH UMMUL QURO AL-ISLAMI BOGOR (DIRAASAH HAALIYYAH ‘AN ‘ILMI AL-MAHFUDZAAT) - Asriani; Resty Nurma Hadiyanti; Emnis Anwar (Program Studi Pendidikan Bahasa Arab, 2021)
Arabic is one of the foreign languages that many people have recently practiced to study and analyze, both of which are geared towards a normative and spiritual approach with the belief that Arabic is a religious language because the Qur’an was also revealed in Arabic. Through a comprehensive educational approach, whoever believes that the Arabic language is a language that deserves to be studied deeply in order to know its historical and aesthetic studies. Islamic Villages Bogor. These problems will be analyzed so that they can be fixed and solutions to overcome them in the future. This research is a qualitative research that uses data collection techniques in the form of observation, interviews and documentation. The results showed the following: 1) learning the Arabic language percussion skill for the eighth grade students in the secondary school for girls. The learning process begins with planning and implementation. The methods that educators use are lectures, vocabulary and assessment. Finally, the educator provides motivation and assessment for individual or group learning assignments, mid-term exams, and final-semester exams. 2) Learning problems for the skill of reading in the case studies of the archives subject include students: 1) Lack of interest in learning the Arabic language. 2) Lack of educational experience at the previous level of education. Students' efforts to enjoy learning Arabic is by opening dictionaries frequently and studying Muhadtha